Effects of short story reading on efl narrative writing - Bùi Thanh Minh Quang (Trường Đại học Trà Vinh, 2019)
The purpose of this study is to examine the effects of short story reading on the improvement of grammar and global quality in EFL narrative writing. In addition, the study also explores learners’ attitudes toward the effect of short story reading on their narrative writing performance.